AI: Initial Responses, More Questions - Scott, Rachel E; Fernandez, Michael (Library resources & technical services, 2025)
Librarians working in technical services have long had opportunities to automate portions of their work. Attitudes about doing so, however, have been mixed. Automation comes with enhanced needs for human-mediated quality control. With this long-standing and somewhat fraught relationship in mind, we began discussing the use of artificial intelligence (AI) and large language model (LLM) tools and their implications for writing and reviewing in Library Resources & Technical Services (LRTS) back in 2023.